2018
DOI: 10.1111/dom.13457
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin compared with glimepiride in metformin‐treated patients with type 2 diabetes: 208‐week data from a masked randomized controlled trial

Abstract: In patients with type 2 diabetes, empagliflozin 25 mg as add-on to metformin for 208 weeks reduced HbA1c with a significantly lower risk of hypoglycaemia and a significantly smaller proportion of patients receiving rescue therapy compared with glimepiride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…The proportion of participants with confirmed hypoglycaemia was somewhat higher with empagliflozin than with placebo; however, no severe hypoglycaemic events requiring assistance were reported. Participants with T2D are at an increased risk of UTIs and genital infections, and some studies have indicated that SGLT2 inhibitors may be associated with events consistent with UTIs, genital infections and volume depletion . In this trial, the frequency of events consistent with UTIs did not differ between empagliflozin and placebo, whereas the proportion of participants with events consistent with genital tract infections was higher with empagliflozin than placebo.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The proportion of participants with confirmed hypoglycaemia was somewhat higher with empagliflozin than with placebo; however, no severe hypoglycaemic events requiring assistance were reported. Participants with T2D are at an increased risk of UTIs and genital infections, and some studies have indicated that SGLT2 inhibitors may be associated with events consistent with UTIs, genital infections and volume depletion . In this trial, the frequency of events consistent with UTIs did not differ between empagliflozin and placebo, whereas the proportion of participants with events consistent with genital tract infections was higher with empagliflozin than placebo.…”
Section: Discussionmentioning
confidence: 55%
“…Participants with T2D are at an increased risk of UTIs and genital infections, 24,25 and some studies have indicated that SGLT2 inhibitors may be associated with events consistent with UTIs, genital infections and volume depletion. [26][27][28] In this trial, the frequency of events consistent with UTIs did not differ between empagliflozin and placebo, whereas the proportion of participants with events consistent with genital tract infections was higher with empagliflozin than placebo. Finally, there may be an increased risk of developing diabetic or euglycaemic ketoacidosis with SGLT2 inhibitor treatment, 29,30 as SGLT2 inhibitors increase glucagon levels and ketone body formation, while clearing glucose via renal excretion.…”
Section: Discussionmentioning
confidence: 58%
“…A total of 27 trials fulfilling the inclusion criteria was identified (Figure S1 and Table S1). The retrieved trials comprised 27 744 and 20 441 patients in SGLT‐2 inhibitor and comparator groups, respectively, with a mean duration of treatment of 84 weeks. Mean age, duration of diabetes, baseline HbA1c and BMI of enrolled patients at baseline were 59.0, 8.3 years, 8.0% and 30.9 Kg/m 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A 4‐year head‐to‐head study (EMPA‐REG H2H‐SU), conducted in T2D patients inadequately controlled on metformin alone (baseline HbA1c 7%‐10%), looked specifically at the relationship between hypoglycemia and fracture risk, comparing the SGLT2 inhibitor empagliflozin (25 mg) vs glimepiride (1‐4 mg), as add‐on to metformin. Hypoglycemic events occurred in 28% of patients on glimepiride vs only 3% on empagliflozin; however, bone fracture occurrence was similar across the groups (4.1% in empagliflozin group; 4.2% in glimepiride group) . In the ACCORD BONE study, intensive glycemic control with any SU was not associated with a higher risk of falls or fracture, in spite of more hypoglycemic episodes .…”
Section: Drugs and Bonementioning
confidence: 88%
“…239,240 Recently, it was reported that the activation of the NLRP3 inflammasome in human mesenchymal stem cells, a major pathway involved in β-cell failure and multiple complications of T2D, also impairs osteogenic differentiation and promotes adipocyte differentiation. 246 Therefore, new SU molecules have been designed to target both the KATP channels and NLRP3 activation, 247 262 ; however, bone fracture occurrence was similar across the groups (4.1% in empagliflozin group; 4.2% in glimepiride group). 263 In the ACCORD BONE study, intensive glycemic control with any SU was not associated with a higher risk of falls or fracture, in spite of more hypoglycemic episodes.…”
Section: Skeletal Effects: In Vitromentioning
confidence: 99%